Regulation of signaling pathways by β‐elemene in cancer progression and metastasis. Issue 8 (25th March 2019) - Qureshi, Muhammad Z.; Attar, Rukset; Romero, Mirna A.; Sabitaliyevich, Uteuliyev Y.; Nurmurzayevich, Sadykov B.; Ozturk, Ozlem; Wakim, Lara H.; Lin, Xiukun; Ozbey, Ulku; Yelekenova, Armida Bakhytbekovna; Farooqi, Ammad A.
Abstract: Entry of β‐elemene into various phases of clinical trials advocates its significance as a premium candidate likely to gain access to mainstream medicine. Based on the insights gleaned from decades of research, it seems increasingly transparent that β‐elemene has shown significant ability to modulate multiple cell signaling pathways in different cancers. We partition this multicomponent review into how β‐elemene strategically modulates various signal transduction cascades. We have individually summarized regulation of tumor necrosis factor related apoptosis‐inducing ligand, signal transducers and activators of transcription, transforming growth factor/SMAD, NOTCH, and mammalian target of rapamycin pathways by β‐elemene. Last, we will discuss the results of clinical trials of β‐elemene and how effectively we can use these findings to stratify patients who can benefit most from β‐elemene. Abstract : We have individually summarized regulation of tumor necrosis factor related apoptosis‐inducing ligand, signal transducers and activators of transcription, transforming growth factor/SMAD, NOTCH, and mammalian target of rapamycin pathways by β‐elemene. Lastly, we will discuss the results of clinical trials of β‐elemene and how effectively we can use these findings to stratify patients who can benefit most from β‐elemene.